Influence of fly ash on the compressive strength of concrete containing recycled aggregate. Issue 3 (3rd September 2019) - Wu, Yaopeng; Gao, Kaixuan; Wu, Bo
Abstract : It is well known that the mechanical properties of concrete containing recycled aggregate (RA) are generally inferior to those of concrete made with natural aggregate. The residual compressive strength of concrete after exposure to high temperature and freeze–thaw cycling was investigated experimentally, and the influence of adding fly ash (FA) was examined. Two hundred and twenty-eight 100 mm cubes were compression-tested to failure. The water/binder (w/b) ratios tested were 0·34, 0·40 and 0·50. The RA replacement levels were 0, 30, 50, 70 and 100%, and the FA replacement levels were 0, 30 and 50%. The high-temperature exposure was 3 h at 400°C. Fifteen cycles of freezing to −18°C and thawing to +5°C were applied. Increasing the w/b ratio or the FA or RA content generally weakened the concrete. FA in the mix minimized to some extent the adverse effect of exposure to high temperature, but the concrete's freeze–thaw performance was poorer with FA in the mix.